Prevalence and risk factors of peri‐implant diseases at patient‐level: A cross‐sectional study in Syria - Asmaa A. A. Aljalloud; Suleiman Dayoub; Yasser Alsayed Tolibah (Wiley, 2023)
Abstract Objectives This research aims to assess the prevalence of peri‐implant diseases and to analyze variables of the probable risk at the patient level associated with the occurrence of peri‐implant diseases in Syrian patients. Materials and Methods A cross‐sectional study has been carried out on 142 patients with 380 dental implants placed between 2015 and 2021. Patients were invited by phone to return to Damascus University's Periodontology Department for clinical and radiological examination. A descriptive statistical analysis was implemented for the prevalence of peri‐implant diseases at the level of the patients. Also, the peri‐implant diseases' factors of risk were determined by the multivariate analytical model. Results The prevalence rate of peri‐implant mucositis and peri‐implantitis in patients was 58.5% and 25.4%, respectively. Peri‐implant disease is associated with multivariate risk indices, gender female (peri‐implant mucositis [OR = 0.269; 95% CI: 0.131−0.552] and peri‐implantitis [OR = 0.561; 95% CI: 0.561−0.216]), diabetes (peri‐implant mucositis [OR = 3.4; 95% CI: 1.73−12.73]), periodontitis (peri‐implant mucositis [OR = 2.409; 95% CI: 1.760−2.613], peri‐implantitis [OR = 10.445; 95% CI: 4.097−26.629]). Conclusions Peri‐implant diseases are common in the Syrian community. Several patient‐level variables (gender female, diabetes, and periodontitis) are associated with peri‐implant disease.